ANALYSIS OF HYDROCARBON TREATING SYSTEM ON PERFORMANCE OF SPARK-IGNITION FOUR-STROKE ENGINES - NUGROHO, SONI (2011)
Air-fuel mixture in a low air fuel ratio is the main factor that can be manipulated to increase torque and decrease fuel consumption of internal combustion engine but it is difficult to do. One difficulty derived from the fact that if the air-fuel ratio is lowered to the point where the entire fuel charge is consumed during idle rotation, it is difficult to sustain reliable ignition of the charge. The research investigates the effect of using Hydrocarbon Treating System on spark ignition engine (SI engine) performance and fuel consumption. A four stroke, single cylinder SI engine was used for conducting this study. Performance tests were conducted for engine torque, power and Specific Fuel Consumption (SFC) using HTS with different number of flow rate 0 cc/s, 1.5 cc/s, 2.0 cc/s, 2.5 cc/s and 3.0 cc/s at varying engine speed condition. The result showed that Hydrocarbon Treating System decrease fuel consumption. Fuel consumption of the engine decreases while the flowrate of the HTS increases. The HTS with the flowrate of 20 cc/s gave the best results for all measured parameters at all mean average values.